2007
DOI: 10.1128/jvi.00308-07
|View full text |Cite
|
Sign up to set email alerts
|

Productive Human Immunodeficiency Virus Type 1 Assembly Takes Place at the Plasma Membrane

Abstract: Gag proteins are necessary and sufficient to direct human immunodeficiency virus type 1 (HIV-1) particle assembly and budding. Recent evidence suggests that Gag targeting to late endosomal/multivesicular body (LE/MVB) compartments occurs prior to viral particle budding at the plasma membrane (PM). However, the route that Gag follows before reaching its steady-state destinations still remains a subject of debate. Using a subcellular fractionation method that separates PM from LE/MVB combined with pulse-chase la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 59 publications
4
95
0
1
Order By: Relevance
“…First, Gag can initiate and complete assembly at the plasma membrane. This is thought to occur predominantly in T lymphocytes, and this process is supported by several lines of evidences: (i) disruption of endosomal trafficking with drugs does not prevent viral production (26,27); (ii) ESCRT complexes can be recruited at the plasma membrane, at sites where Gag accumulates (28 -30); (iii) Gag can be seen multimerizing and budding from the plasma membrane in live cells (31). Second, Gag could initiate assembly in endosomes, and then traffic to the cell surface to be released.…”
mentioning
confidence: 70%
“…First, Gag can initiate and complete assembly at the plasma membrane. This is thought to occur predominantly in T lymphocytes, and this process is supported by several lines of evidences: (i) disruption of endosomal trafficking with drugs does not prevent viral production (26,27); (ii) ESCRT complexes can be recruited at the plasma membrane, at sites where Gag accumulates (28 -30); (iii) Gag can be seen multimerizing and budding from the plasma membrane in live cells (31). Second, Gag could initiate assembly in endosomes, and then traffic to the cell surface to be released.…”
mentioning
confidence: 70%
“…We have previously observed a population of VLPs that move rapidly in and out the field adjacent to the plasma membrane and we have demonstrated that these are also labeled with markers for internal endocytic compartments including clathrin and CD63 (18) Several lines of evidence indicate that these endosome-localized particles are not productive preassembly intermediates (15,16,28).…”
Section: Dynamics Of Hiv-1 Rna Molecules At the Plasma Membrane Of Cellsmentioning
confidence: 99%
“…The productive site of HIV-1 assembly is the plasma membrane, both in cultured cell lines and primary cells (15)(16)(17). This makes the assembly of HIV-1 accessible to imaging with totalinternal-reflection (TIR) fluorescent microscopy, which selectively excites fluorophores in close proximity (ϷϽ70 nm) to the coverslip.…”
Section: Rna Packaging ͉ Virion Morphogenesismentioning
confidence: 99%
“…HIV-1 Gag targeting to the plasma membrane (PM) 2 is critical for proper and efficient assembly to produce progeny virions (1,(3)(4)(5)(6)(7)(8)(9). During virus maturation, Gag is cleaved into myristoylated matrix (myr(ϩ)MA), capsid, and nucleocapsid proteins, inducing major morphological reorganization of the virus (1,2,4,5,10).…”
mentioning
confidence: 99%